Use of Phenacyl Thiosalicylates for the Preparation of 3-Hydroxybenzo[b]thiophene Derivatives - Trapani, Patricia; Kvapil, Lubomír; Hradil, Pavel; Soural, Miroslav (Synlett, 2018)
In this work, we attempted to synthesize thioflavonols using rearrangement of phenacyl thiosalicylates prepared by two different approaches and subjected to cyclization under acidic conditions. Contrary to our expectations, the isolated products were identified as (3-hydroxybenzo[b]thiophen-2-yl)(phenyl)methanones. The detailed reaction mechanism was elucidated by characterization of all reaction intermediates with HPLC and NMR spectroscopy. The applicability of the reaction using different phenacyl esters was tested.
Keywords: rearrangement; heterocycles; benzo[b]thiophene; thiosalicylates; bromoketones